2009
DOI: 10.1002/polb.21872
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbon nanotubes on dynamic mechanical property, thermal property, and crystal structure of poly(L‐lactic acid)

Abstract: Effects of carbon nanotubes (CNT) on the dynamic mechanical property, thermal property, and crystal structure of poly(L-lactic acid) (PLLA) were investigated. Dynamic mechanical analysis (DMA) found that CNT via grafting modification with PLLA (CNT-g-PLLA) could result in effective reinforcing effects. Tan d of DMA found that CNT-g-PLLA was compatible with the PLLA matrix, giving a single T g of the composite with a higher CNT-g-PLLA loading giving a higher T g of the composite. Wide angle X-ray diffraction (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
37
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 42 publications
3
37
1
Order By: Relevance
“…224 In polylactide an increase in the equilibrium melting temperature was reported, but the authors attributed this to a problem with the classical treatment since the equilibrium melting temperature for the pure material was much lower than that presented in the literature. 202 In syndiotactic polystyrene, no change was found for T 0 m , 168 while an increase was found for poly(3-hydroxybutyrate-co-3-hydroxyvalerate). 225 Melting of polyethylene crystals above the equilibrium melting temperature was found for a sample with a very high volume fraction of nanotubes which the authors attributed to melting of surface crystallites, that is, a transition from a nematic liquid crystalline phase to an isotropic phase at the nanotube-polymer interface.…”
Section: Semicrystalline Polymersmentioning
confidence: 95%
See 3 more Smart Citations
“…224 In polylactide an increase in the equilibrium melting temperature was reported, but the authors attributed this to a problem with the classical treatment since the equilibrium melting temperature for the pure material was much lower than that presented in the literature. 202 In syndiotactic polystyrene, no change was found for T 0 m , 168 while an increase was found for poly(3-hydroxybutyrate-co-3-hydroxyvalerate). 225 Melting of polyethylene crystals above the equilibrium melting temperature was found for a sample with a very high volume fraction of nanotubes which the authors attributed to melting of surface crystallites, that is, a transition from a nematic liquid crystalline phase to an isotropic phase at the nanotube-polymer interface.…”
Section: Semicrystalline Polymersmentioning
confidence: 95%
“…123 Peaks in small-angle scattering experiments generally shift towards lower angles indicative of thicker crystals with the introduction of nanotubes. 222,226 However, a very detailed analysis of small-angle scattering patterns for polylactide found a decrease in crystal thickness with the introduction of nanotubes 202 while another study also found a decrease in thickness for polybutylene succinate. 184 In a study where the rate of crystallization in an isothermal experiment was much smaller for nanotube-filled polyethylene oxide versus the unfilled polymer, the crystal thickness varied with the level of nanotubes in no obvious pattern.…”
Section: Semicrystalline Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…In other series of experiments, the cooling rate from the melt was increased up to 40 C min À1 for all the samples ( Fig. 8a and b).…”
mentioning
confidence: 92%